Algorithm For Examining Pregnant Women With Cervical Pathology To Exclude Cancer - Yakubbekova Sokhibahon Sadik kizi (Genius Journals, 2025)
Cervical cancer is the most common malignancy associated with pregnancy. The management of patients with this disease is a unique and complex clinical situation, due to the unpredictable behavior of the tumor during pregnancy and the impossibility of performing all necessary diagnostic and therapeutic measures. It is impossible to perform all necessary diagnostic and therapeutic procedures. Pregnancy is a factor that triggers tumor development due to hormonal changes, decreased immune defenses, improved blood and lymph flow to the reproductive organs, and postpartum cervical changes. Diagnosing cervical cancer during pregnancy is particularly challenging due to the high risk of under- or overdiagnosis, as well as the unavailability of many diagnostic methods. When examining patients, it is necessary to carefully differentiate between normal and pathological growth processes during pregnancy
Keywords: Pregnancy; cervical cancer; CIN